Enhancing the performance of cold bitumen emulsion mixture using supplementary cementitious materials - Nassar, Ahmed Izat Mohammed (2016)
Several benefits are gained from using cold mix asphalt (CMA) instead of hot mix asphalt (HMA). The benefits include conservation of materials and reducing energy consumption, preservation of the environment and reduction in cost. One of the common types of CMA is cold bitumen emulsion mixture (CBEM) which is the mixture produced by mixing mineral aggregate with bitumen emulsion. Despite the efforts applied in the last few decades in order to improve and develop CBEM utilization, certain deficiencies remain that make it inferior to HMA, resulting in restricting or minimizing of its use. However, the development of CBEM for road construction, rehabilitation and maintenance is steadily gaining interest in both pavement engineering industrial and research sectors.